2021
DOI: 10.3389/fmed.2021.756210
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Prognostic Value of Aspartate Aminotransferase-to-Platelet Ratio Index in Patients With Hepatocellular Carcinoma: Meta-Analysis of 28 Cohort Studies

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors globally; it is valuable to predict its prognosis after treatment. Aspartate aminotransferase-to-platelet index (APRI), a non-invasive biomarker consists of two routine test parameters easily available in all the patients. Our study aimed to investigate whether APRI can serve as an independent prognostic marker in the patients with HCC.Methods: We extensively searched PubMed, Embase, and Web of Science databases on June 20, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Some studies have indicated that patients with severe sepsis/septic shock have lower platelet count [12]. The prognostic ability of platelet count-related indices has been investigated in a variety of diseases, such as cancers, sepsis and liver cirrhosis [13][14][15][16]. The platelet count-related ratios may be a more promising biomarker of inflammation than conventional indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that patients with severe sepsis/septic shock have lower platelet count [12]. The prognostic ability of platelet count-related indices has been investigated in a variety of diseases, such as cancers, sepsis and liver cirrhosis [13][14][15][16]. The platelet count-related ratios may be a more promising biomarker of inflammation than conventional indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, it is worth mentioning that there were other biomarkers not only inflammatory ones, such as APRI and CRP. It is reported that high APRI levels are associated with poor OS and DFS in the patients with HCC, and pretreatment APRI can be used as an independent prognostic factor, but it is necessary to incorporate other predictive prognostic systems to ensure accuracy ( 69 ). Furthermore, the significance of CRP has been demonstrated as a predictor of survival in HCC, but the current opinion on the prognostic role of CRP in HCC is still controversial ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The above findings suggest that most of our patients developed significant fibrosis/cirrhosis at the time of presentation. As already known, a high FIB 4 score [ 31 ] or APRI score [ 32 , 33 ] has been associated with poor survival. This further confirms the fact that most HCC patients present late and thus have a poor prognosis at the time of presentation.…”
Section: Discussionmentioning
confidence: 99%